ENT300: general guideline for business plan writing (part 2) - Nik Jaafar, Nik Fazlin Hiryati; Nik Hassan, Nik Fakrulhazri; Ibrahim, Norlaila; Md Noor, Jannah Munirah; Jasni, Nur Syuhada (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
Besides the overall structure and the look of a business plan, the content is very important to convince readers. Discussed below are among the matters that must be taken care of to produce a good business plan. (Note: The 1st 7 subtopics have appeared in the previous edition of BizNewz).